ACUTE CORONARY SYNDROME: EFFECT OF MYOCARDIAL REVASCULARIZATION AND COMPLEX THERAPY ON CARDIAC REMODELING, SYSTOLIC-DIASTOLIC DYSFUNCTION AND CARDIAC COMPLICATIONS - Denesіuk, О.V. (World of Medicine and Biology, 2015)
The article presents the results of a long study of the effect of myocardial revascularization, bisoprolol, perindopril and antiplatelet drugs on the status and function of the myocardium and for cardiovascular disease. In examined patients after myocardial revascularization, and prolonged use of drug treatment caused a decrease eccentric left ventricular hypertrophy, and marked increase in angina attacks and symptoms of heart failure, although there was a slight decrease in ventricular fibrillation, atrial fibrillation, AV - blockades and left bundle branch block.
Keywords: acute coronary syndrome; heart remodeling; invasive and drug therapy